Propylaea of the Roman Forum in Tergeste: Origins and Meanings of the Architectural Form - Mikhailova, Ekaterina M. (Actual Problems of Theory and History of Art, 2023)
The complex of the Roman forum in Tergeste (modern Trieste) includes an element uncommon for the architecture of the Early Roman Empire — propylaea with projecting wings and rich sculptural decoration. This monument, some elements of which were discovered as early as in the 17th century, has extensive historiography, thanks to step-by-step archaeological research, complicated by the fact that the propylaea were built into the medieval belfry of the Cathedral of Trieste. The article develops and complements previously made observations regarding the architecture and decoration of the propylaea, combining semantic analysis of the reliefs with the analysis of the architectural form which seems unique not just for Northern Italy but for the Roman Imperial architecture of the 1st century in general.The first hypothesis supposes that this form originated from such representative Athenian monuments of the Classical period as Mnesikles’ Propylaea and the stoa of Zeus Eleutherius, where projecting wings with columns appeared for the first time. However, considering the territorial and chronological distance and the absence of evidence for a specific link between Tergeste and Athens, it might be assumed that this form refers to Hellenistic propylaea. Nevertheless, we should note that, regarding their plan and proportions, most of those gates with projecting wings have very little in common with the compact plan of the Trieste monument — rather, they resemble long stoae. The article attempts to trace the possible origins of this architectural form in the Roman and Hellenistic world, analyze its possible variations and meanings, taking into account the relief decoration of the monument.
Keywords: Trieste; Tergeste; Istria; propylaea; Roman forum; monumental gates; Roman Imperial architecture; Hellenistic altars; stoa with projecting wings; memorial architecture